Crystal structure of human CK2α at 1.06 Å resolution. (1st October 2013) - Kinoshita, Takayoshi; Nakaniwa, Tetsuko; Sekiguchi, Yusuke; Sogabe, Yuri; Sakurai, Atsushi; Nakamura, Shinya; Nakanishi, Isao
<x xml:space="preserve">Abstract</x> The Ser/Thr kinase CK2 consists of two catalytic subunits (CK2α) and a dimer of the regulatory subunits (CK2β), and is a ubiquitous enzyme that regulates growth, proliferation and the survival of cells. CK2 is a remarkable drug target for potentially treating a wide variety of tumours and glomerulonephritis. The purified CK2α protein was crystallized using ethylene glycol as a precipitant. The crystal structure of CK2α with 21 loci of alternative conformations, including a niacin, 19 ethylene glycols and 346 waters, was determined at 1.06 Å resolution to an Rwork of 14.0% (Rfree = 16.5%). The alternative ensemble in the internal hydrophobic core underpins the plasticity of the αD‐helix responsible for the regulation of ATP/GTP binding. The clear density map indicates that a niacin molecule, contained in the Escherichia coli culture medium, binds to the ATP binding site. An ethylene glycol molecule binds in the hydrophobic pocket lateral to the αD‐helix forming the rim of the active site. The other ethylene glycol molecules occupy physiologically significant sites, including the CK2β binding interface and substrate binding site, as well as the gap in the crystal packing. Together with water molecules in the active site, these structural insights should facilitate drug discovery.